Pengaruh Environmental Perfomance dan Corporate Social Perfomance Terhadap Economic Perfomance - Imma Maharani Fitriah; Dirvi Surya Abbas; Wati Yarahmah (Akuntansi, 2023)
The purpose of this study is to determine the effect of Environmental Perfomance and Corporate Social Perfomance on Economis Perfomance in the Manufacturing companies listed on the Indonesia Stock Exchange. The research time period used is 2016-2021 period. The population of this study includes all companies listed on the Indonesia Stock Exchange for the period 2016-2021. The sampling technique used was the Non Probability Sampling technique. Based on the predetermined criteria obtained 11 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis using the eviews 9.0 data processing program. The result of the study show that Environmental Perfomance has an effect on Economic Perfomance. Corporate Social Perfomance has no effect on Economic Perfomance.